Antidepressant Prescribing Trends for Adults With and Without Autism in the United Kingdom From 1997 to 2023: A Population‐Based Cohort Study Using Clinical Practice Research Datalink Aurum - Aws Sadik; Golam M. Khandaker; Antonio F. Pardiñas; Michael Lundberg; Brian K. Lee; Cecilia Magnusson; Dheeraj Rai; Paul Madley‐Dowd (Autism Research, 2026)
ABSTRACT Antidepressant prescribing and autism diagnoses have increased in recent years. We aimed to describe and compare trends in antidepressant prescribing, indications, doses and durations in autistic and non‐autistic males and females in the United Kingdom (UK) from 1997 to 2023. Using population‐representative UK primary care records, we defined three autistic groups—autistic adults with intellectual disability (ID), autistic adults without ID and all autistic adults—and four non‐autistic groups. In each calendar year we calculated: annual, lifetime and new antidepressant prescribing; indications for serotonin‐selective reuptake inhibitor initiation; average doses prescribed for citalopram, fluoxetine, and sertraline; and the proportion of courses that lasted over 1, 2, and 3 years. We also repeated analyses with sex‐stratification. In all, 34,173,295 non‐autistic adults and 172,242 autistic adults were included (47,011 with ID and 125,231 without ID). 30% of autistic adults and 14.7% of non‐autistic adults were prescribed an antidepressant in 2023. Prescriptions, doses and course durations increased over time for all groups. Prescriptions were highest in autistic adults without ID and females, whereas course durations were highest in autistic adults with ID. Recording of depression and anxiety as indications was lower for those with ID. Antidepressant prescribing has increased more for autistic adults than non‐autistic adults since 1997, with more new starters, higher doses and longer course durations. This potentially increases the risk of adverse medication effects for autistic adults and emphasizes the need for stronger evidence around the effectiveness and tolerability of mental health interventions and the reasons for systematic differences in prescribing.